Mealybugs as pests of flower and medicinal crops: An Overview - Vijay, S; Lisha, J Mary; Vinoth, R (Indian Journal of Plant Protection, 2020)
Mealybugs belong to the insect sub order homoptera and the super family coccoidea. They cause direct damage by feeding and indirectly by injecting toxic saliva, excreting honey dew giving an ugly look to the entire crop, resulting in poor quality of the produce. It also causes yellowing of leaves and malformation of affected portions due to salivary infection. Of the known 35 families under Coccoidea, 20 families are recognized only in India of which, pseudococcidae is widely prevalent. However, at times mealy bug infestation may occur within the vegetative shoot apex and may be extremely difficult to detect. This ability of mealybugs to form dense colonies particularly with in the shoot apex often makes chemical control of this pest quite difficult. Among the various coccids Phenacoccus solenopsis Tinsley (Solenopsis mealybug) has been recorded causing economic damage to many crops. Now a days mealybug infestation leads to severe outbreaks in many crops. In India, losses have been reported in cotton, bhendi, gingelly, sunflower, brinjal, chrysanthemum, marigold and tuberose resulting in reducing yields up to 50 to 100 per cent. The other mealy bugs are Maconeliococcus hirsutus (Green) (Grapevine mealy bug), Phenacoccus solani Ferris (Solanum mealybug), Phenacoccus madeirensis (Green) (Maderia mealybug), Nipaecoccus viridis (Green) (lebbeck mealybug), Coccidohystrix insolita (Green) (Brinjal mealybug), Dysmicoccus brevipes (Ckll.) (Pine apple mealybug), Rastrococcus iceryoides (Green) (Icerya mealybug), Paracoccus marginatus Williams and Granara de Willink (Papaya mealybug) and Planococcus citri (Risso) (Citrus mealybug) cause a severe damage by reducing the photosynthesis of the plant due to honeydew secretion and sooty mould attack in agricultural and horticultural crops.